Kepemimpinan Keluarga Dalam Kajian Kontekstual - Zenrif, MF (Musawa Jurnal Studi Gender dan Islam, 2004)
The problem of family leadership is heatedly debated: "should there only man or woman to hold the position as the head of a family?" This article offers some alternatives on the reformulation of the concept of family leadership from the Islamic perspective. Even though the topic was discussed by both classical and modem ulama, a comprehensive analysis on the leadership of women in a family is required. This article is meant to offer some models in empowering women.